The Collected Works of James Wm. McClendon, Jr. : Volume 2 - McClendon, James William (Book collections on Project MUSE., 2014)
James Wm. McClendon, Jr. was the most important "baptist" theologian of the twentieth century. McClendon crafted a systematic theology that refused to succumb to the pressures of individualism, grew out of the immediacy of preaching the text, and lamented the stunted public witness of a fractured Protestant ecclesiology. This two-volume set mixes previously unpublished and published lectures and essays with rare and little known works to form a representative collection of the essential themes of McClendon's work. The first volume focuses on the philosophical and theological shifts leading to McClendon's articulation of the baptist vision. The second volume specifically elucidates the more philosophical themes that informed McClendon's work, including ways in which these themes had immediate theological import. Taken together, the set provides the most comprehensive presentation of McClendon's work now available, revealing the sustained and systematic character of his vision over the course of his life. These two volumes will provide scholars, preachers, and students with McClendon's radical, narrative, and connective theology.